2016
DOI: 10.1063/1.4954739
|View full text |Cite
|
Sign up to set email alerts
|

Thermal transport size effects in silicon membranes featuring nanopillars as local resonators

Abstract: Silicon membranes patterned by nanometer-scale pillars standing on the surface provide a practical platform for thermal conductivity reduction by resonance hybridization. Using molecular simulations, we investigate the effect of nanopillar size, unit-cell size, and finite-structure size on the net capacity of the local resonators in reducing the thermal conductivity of the base membrane. The results indicate that the thermal conductivity reduction increases as the ratio of the volumetric size of a unit nanopil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 38 publications
3
50
0
Order By: Relevance
“…They confirmed that nanopillars could reduce the thermal conductivity by 50% and demonstrated that this reduction depends on the pillar diameter and the ratio of the pillar volume to that on the membrane within a unit cell [33]. This conclusion was confirmed by Honarvar et al [57]. …”
Section: Simulations Of Heat Conductionmentioning
confidence: 76%
See 1 more Smart Citation
“…They confirmed that nanopillars could reduce the thermal conductivity by 50% and demonstrated that this reduction depends on the pillar diameter and the ratio of the pillar volume to that on the membrane within a unit cell [33]. This conclusion was confirmed by Honarvar et al [57]. …”
Section: Simulations Of Heat Conductionmentioning
confidence: 76%
“…Usually, researchers tentatively attribute the thermal conductivity reduction to the impact of local resonances on the phonon dispersion [3234,55,57,58]. Indeed, the occurrence of the local resonances was demonstrated by different simulation techniques [30,38,55,58], and since the local resonances flatten the dispersion branches (Figure 1), the average group velocity becomes lower [32,33,57]. Hence, this effect can be linked to the thermal conductivity reduction.…”
Section: Simulations Of Heat Conductionmentioning
confidence: 99%
“…The physical origin of phononic and photonic band gaps can be understood at micro-scale using the classical wave theory to describe the Bragg and Mie resonances, respectively, based on the scattering of mechanical and electromagnetic waves propagating within the crystal 17 . PCs have many applications, such as vibration isolation technology [18][19][20][21][22] , acoustic barriers/filters [23][24][25] , noise suppression devices [26][27] , surface acoustic devices 28 , architectural design 29 , sound shields 30 , acoustic diodes 31 , elastic metamaterials [21][22]25,27,32 and thermal metamaterials [33][34][35][36][37][38][39] . There are also smart PCs that have been studied, such as piezoelectric [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] , piezomagnetic [55][56][57][58] an...…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, researches have used PCs on the scale µm 10,17,64,65 and mm, resulting in band gaps ranging from GHz and kHz to MHz, respectively. More recently, with the advance of nanomaterials fabrication, nanophononic crystals have been studied and it is possible to control wave propagation in a frequency range from hypersonic [3][4][5][6][66][67][68][69][70][71][72][73][74][75] to thermal [33][34][35][36][37][38][39] . However, nano-piezoelectric PCs have not been investigated yet even though studies about nano-piezoelectric materials have been reported [76][77][78][79] .…”
Section: Introductionmentioning
confidence: 99%
“…The physical origin of phononic and photonic band gaps can be understood at micro-scale using the classical wave theory to describe Bragg and Mie resonances, respectively, based on the scattering of mechanical and electromagnetic waves propagating within the crystal 17 . PCs have many applications, such as vibration isolation technology [18][19][20][21][22] , acoustic barriers/ filters [23][24][25] , noise suppression devices 26,27 , surface acoustic devices 28 , architectural design 29 , sound shields 30 , acoustic diodes 31 , elastic/acoustic metamaterials 21,22,25,27,32 (EM/AM), also known as locally resonant phononic crystals (LRPC), and thermal metamaterials [33][34][35][36][37][38][39] (TM), also known as phononic thermocrystals or locally resonant phononic thermocrystals.…”
Section: Introductionmentioning
confidence: 99%